(untitled) (UNED Research Journal, 2013)
Feeding ecology of Great Egret Ardea alba (Pelecaniformes: Ardeidae) in a wetland of the Paraná River, Argentina. Herons as a group have contributed substantially to the field of evolutionary ecology through studies that have helped elucidate mechanisms that allow coexistence of sympatric species. Detailed descriptions of feeding ecology are essential for understanding mechanisms of coexistence. Despite being one of the most common species in Argentina, detailed studies on the feeding ecology of Great Egrets Ardea alba are scarce. We studied Great Egret feeding ecology through an analysis of the stomach contents of 38 individuals captured between 1990 and 1993 in a wetland on the Paraná River, Argentina. The diet included a total of 33 taxa, with fishes as the predominant prey item. The predominance of fishes in the diet agrees with results of previous studies. There was, however, no evidence of dietary selectivity. The largest proportion of prey (40%) were 21 – 30mm in length. Distribution of prey sizes differed between the Great Egret and the sympatric and congeneric Cocoi Heron (Ardea cocoi).Great Egrets primarily foraging in areas characterized by aquatic vegetation and in areas with open water. KEY WORDS Ardea alba, Ardeidae, diet, Great Egret, Paraná river, stomach content, wetland.